Competence development and employability expectations: A gender perspective of mobility programmes in higher education - Francisca Rosa Álamo-Vera; Lidia Hernández-López; José Luis Ballesteros-Rodríguez; Petra De Saá-Pérez (Administrative Sciences, 2020)
This paper analyses the role of study-abroad programmes in higher education by examining how students' participation can foster competence development and employability expectations. Our research focuses on the acquisition of competences through the international mobility programme Erasmus+ of 191 students of an undergraduate programme in tourism, considering the different perceptions of male and female students. Our results confirm that five out of the six competences which students develop through Erasmus+ mobility have a positive and significant influence on their employability expectations. Our findings also confirm that male and female students have different perceptions concerning the influence on their employability expectations of those competences acquired during their experience studying abroad.
Keywords: 350; employability competences; Erasmus+; gender; higher education; mobility programmes; tourism